Evaluation of anxiety and depression prevalence in patients with primary severe hyperhidrosis - Gleide Maria Gatto Bragança; Sonia Oliveira Lima; Aloisio Ferreira Pinto Neto; Lucas Menezes Marques; Enaldo Vieira de Melo; Francisco Prado Reis (Anais Brasileiros de Dermatologia, 2014)
BACKGROUND: Primary hyperhidrosis (PH) can lead to mood changes due to the inconveniences it causes. OBJECTIVE: This study aimed to examine the existence of anxiety and depression in patients with severe primary hyperhidrosis who sought treatment at a medical office. METHODS: The questionnaire "Hospital Anxiety and Depression Scale" was used for 197 individuals, in addition to the chi square test and Fisher exact test, p <0.05. RESULTS: There was an increased prevalence of anxiety (49.6%) but not of depression (11.2%) among patients with PH, with no link to gender, age or amount of affected areas. Palmar and plantar primary hyperhidrosis were the most frequent but when associated with the presence of anxiety, the most frequent were the axillary (p = 0.02) and craniofacial (p = 0.02) forms. There was an association between patients with depression and anxiety (p = 0.001). CONCLUSIONS: the involvement of Primary hyperhidrosis was responsible for a higher prevalence of anxiety than that described among the general population and patients with other chronic diseases. Depression had a low prevalence rate, while mild and moderate forms were the most common and frequently associated with anxiety. The degree of anxiety was higher in mild and moderate types than in the severe form.